EKSPLORASI ETNOMATEMATIKA PADA MOTIF TENUN SONGKET MELAYU BUDAYA BATU BARA - Azizah, Isnaini; Ananda, Rusydi (Universitas Swadaya Gunung Jati., 2024)
The aim of this research is to determine the mathematical concepts contained in the Malay Songket Weaving Motifs of Batu Bara Culture. The research method used in this research is descriptive qualitative with an ethnographic approach. The ethnographic approach is an empirical and theoretical approach that aims to obtain a cultural description and analysis through field research. The results of this research found mathematical concepts of geometric shapes which are specifically used in Malay Songket Weaving Motifs, especially in the concept of flat shapes, namely, triangles, rhombuses, ellipses and circles. The concept of Arithmetic Sequences is also found in this Malay Songket Weaving Motif, namely that there are motifs that have the same shape but are found to be repeated. The ethnomatic conclusion is very simple and can be seen clearly in the motifs of Malay Songket Weaving in Batubara Culture